Financial-Stability Challenges in European Emerging-Market Countries - Schinasi, Garry (2012)
This paper examines the financial-stability challenges that will most likely be faced by European emerging-market countries in adapting to the post-crises environment, including the new financial-stability architecture and the other remaining weaknesses revealed by the global and European crises. The paper first reviews the pre-crisis financial-stability architectures in Europe and across the globe and then identifies the key weaknesses revealed by the global crisis. It then describes the micro and macro-prudential components of the new European System of Financial Supervision and some of its design limitations (and only briefly mentions reforms designed to deal with sovereign debt problems). The paper then identifies ten key areas where there are remaining challenges of implementation and additional reforms: six areas pertaining to all countries in Europe as well as the other major financial centers and four areas more germane to emerging-market countries in Europe. In discussing these ten areas, the paper tries to differentiate the relative challenges faced by categories of emerging-market countries, and their possible links to the excessive build-up of vulnerabilities in the pre-crisis period as a potential source of lessons for policy going forward.